Tinjauan Kritis Pergantian Antar Waktu dalam Dinamika Politik Indonesia: Perspektif Demokrasi - Dameanti, Anggi Sihol; Mahendra, Reza; Oktivan, Yori Viski (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
Inter-Time Change (PAW) in the context of Indonesian democracy is often in the spotlight in political dynamics. This research uses normative legal methods with a statutory approach to analyze the legal and political aspects of PAW. The aim of this research is to examine the implications of PAW in the representative democracy system in Indonesia as well as the relationship between council members and political parties. The research results show that PAW is often used as a control tool by political parties over council members who are not in line with party policies. In conclusion, PAW has a strong legal basis but needs a more transparent mechanism so as not to shift the direction of people's representatives to become representatives of the interests of political parties.